Social Actors' Representation at Chaka Zulu's Press Conference: Critical Discourse Analysis - Trisnawati, Dina (English Literature Study Program, 2023)
In June 2022, people in the United States, especially celebrities were shocked by the news of the murder. The manager of actor and rapper Ludacris, Chaka Zulu, was accused as the murderer. With that accusations, he receive various negative reaction from the public. Chaka’s legal team immediately held a press conference to sway public opinion and in that occasion, it could be found social actor representation. Among the many pieces of research regarding social actor representation, research that investigate spoken discourse is rarely carried out. Therefore, this study aims to investigate exclusion and inclusion strategies used by lawyers when representing social actors in press conference. This study uses van Leeuwen’s social actor representation theory (2008). It uses a descriptive-qualitative method to ensure clear data analysis. The data were obtained from the FOX 5 Atlanta YouTube channel. This study reveals that lawyers use exclusion and inclusion. The lawyers used more inclusion than exclusion. Moreover, the most frequent sub-inclusion strategy is role allocation, as active and passive roles allow lawyers to show who is guilty and who is not. Meanwhile, the most frequent exclusion strategy is suppression, it allows lawyers to eliminate actors and emphasize others. Future studies is recommended to explore other van Leeuwen approaches. Future studies can also use other spoken discourse as research topics, for example press conference with public relation or others.